ANALISIS PENGARUH STORE ATMOSPHERE TERHADAP MINAT BELI KONSUMENDI INDOMARET KOTA MATARAM - HADI, SOPAN SOPIAN (Jurnal Magister Manajemen, 2015)
This study aims to investigate the influence of store atmosphere, which consists of a number of variable such as exterior, interior store layouts and pointr of interest display, on the consumers interest to purchase in the Indomaret store in Mataram City. This study uses the theories of marketing management related to store atmosphere and consumers interest to purchase. This study employed an associative approach. A purposive sampling method was used to collect data from 100 respopndents who had already visited Indomaret stores in Mataram City. The instruments for data collection were a questionnaire and documentation study. The data collected were analyzed with a multiple linear regression method. Result of the study show that the variable of general interiot of MataramIndomaret stores influenced very significantly on the counsumers interest to buy. Meanwhile, other variables, such as the shop exterior, store layout, and interior displays a point of interest, did not affect the consumers interest tu buy. Key word : store atmosphere, eksterior toko, store layout, interior point of interest display